Cultural Validation of the Portuguese Version of the Multicultural Mental Health Awareness Scale - MMHAS - Monteiro, Ana Paula Teixeira de Almeida Vieira (2015)
Introduction Cultural competence is an essential component in rendering effective and culturally responsive services to culturally and ethnically diverse clients. Aims The aim of this study was to evaluate the reliability and validity of the Portuguese version of the Multicultural Mental Health Awareness Scale - MMHAS (Khawaja, Gomes &Turner, 2008). Methods After a process of translation and transcultural validation, the Portuguese version of MMHAS, along with a sociodemographic questionnaire, were applied to a sample of 306 Portuguese nurses, aged between 21 and 68 years, with an average age of 35,4 years and a standard deviation of 9.8 years; 25.2% female and 74.8% male. A psychometric research design was used with content and construct validity and reliability. Results The factor analysis confirmed that the MMHAS has a three-factor of multicultural competencies (Cultural Awareness, Cultural Knowledgeand, Cultural Skills) explaining 59.51% of the total variance. The Portuguese version of MMHAS has a strong internal consistency, with a Cronbach's alpha of 0.958 for total scale. Conclusion The results supported the construct validity and reliability of the Portuguese version of MMHAS. The scale can be used to evaluate the effectiveness of the multicultural competency training programs in mental health nursing.